Impact of Body Composition and Physical Function on Quality of Life After Gastrectomy for Gastric Cancer - Wang, Wen-Bin; Song, Hao-Nan; Huang, Dong-Dong; Luo, Xin; Cai, Hui-Yang; Yan, Jing-Yi; Chen, Wei-Zhe; Xing, Chun-Gen; Dong, Qian-Tong; Chen, Xiao-Lei (Frontiers in Surgery, 2022)
Purpose Patients with gastric cancer after gastrectomy often suffer from a decline in their quality of life (QoL), but the relationship between body composition (BC) and physical function on QoL has rarely been studied. This study aims to evaluate and determine the changes in QoL after gastrectomy and the impact of BC and physical function on QoL. Methods A total of 311 gastric cancer patients completed EORTC QLQ-C30 and EORTC QLQ-STO22 questionnaires before and 1, 3, 6 months post-surgery. Data including BC, handgrip strength (HGS) and 6-m gait speed (GS) were collected prospectively. Multiple linear regression analysis was used to determine the correlation between QoL and BC, HGS and GS. Results Patients had significantly worse scores after surgery on most function and symptom scales (p < 0.001), but most of these scales recovered within 6 months after surgery. A higher subcutaneous fat area (SFA)was associated with increased symptom scores 1 month after surgery. A higher GS is associated with a better global health status symptom. Conclusion Patients suffer from a decline in their QoL after gastrectomy for gastric cancer. Intervention strategies aiming at reducing SFA and improving GS may improve the QoL in patients underwent gastrectomy for gastric cancer.